(untitled) (Modern education and development, 2025)
This scoping review examines the significance of grammar in second language teaching and learning. Its primary focus is to synthesize relevant research and literature on grammar acquisition and to identify effective strategies for achieving it. Acquiring grammar involves the subconscious acceptance of grammatical knowledge, which is then utilized in communication. This implicit aspect complicates research efforts, highlighting the need for more information to enhance our understanding. Consequently, this review collected and analyzed recent studies from various databases, including both qualitative and quantitative research. Many language educators emphasize the importance of pedagogic grammar in second language acquisition. The review reveals that the study of grammar acquisition is essential and that further research is necessary to enrich existing knowledge. Such investigations can lead to improved strategies for facilitating grammar acquisition among language learners, ultimately enhancing both second language learning and teaching.